Bioaccumulation of lead, calcium and strontium and their relationships in the Octopus Octopus vulgaris - Seixas, Sónia (2005)
Octopuses (Octopus vulgaris) landed from commercial fishing were sampled and the concentrations of lead, calcium and strontium, in digestive gland, branchial heart, gills, mantle and arms, were determined using PIXE (particle-induced X-ray emission). Lead was detected in all tissues, although not in samples from all animals analysed. Female octopuses accumulated more lead in digestive gland than did males. The digestive gland index, an indicator of nutritional status, showed a negative correlation with lead concentration in both sexes. There were positive correlations between the concentration of lead and those of calcium and strontium in digestive gland and a negative correlation between lead and calcium in branchial heart tissue. Concentrations of calcium in arms were lower in autumn and spring than in winter and summer. Lead content increased with increasing body weight and mantle length so we can conclude that lead continues to accumulate during the animal’s life. Concentrations of lead in two samples were higher than the maximum legally permitted concentration of lead in food.